1994
DOI: 10.1111/j.1600-0773.1994.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Glutathione Monoethyl Ester and Glutathione on Circulating and Hepatic Sulfhydrils in the Rat

Abstract: Glutathione (GSH) plays an important role in the detoxification of reactive metabolites of oxygen and xenobiotics and as a source of cysteine. Since several clinical situations characterized by low circulating and intracellular GSH have been identified, there is a growing interest in pharmacological interventions to correct a deranged sulfhydril status. Therefore, the systemic bioavailability of orally administered GSH and glutathione monoethyl ester (GSHE) was examined in the rat. Following the intraduodenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…In our previous study, supplementation with GSH restored the mucosal GSH/GSSG ratio and abrogated the peroxide-induced suppression of intestinal cell turnover [45]. Another study has indicated that supplementation with low-dose GSH increases hepatic cysteine, the precursor of GSH [46]. Consequently, the results of the present and previous studies indicate that oral chronic administration of GSH might have some antioxidant and anti-carcinogenic properties in rats fed with beef tallow after AOM pretreatment.…”
Section: Discussionsupporting
confidence: 47%
“…In our previous study, supplementation with GSH restored the mucosal GSH/GSSG ratio and abrogated the peroxide-induced suppression of intestinal cell turnover [45]. Another study has indicated that supplementation with low-dose GSH increases hepatic cysteine, the precursor of GSH [46]. Consequently, the results of the present and previous studies indicate that oral chronic administration of GSH might have some antioxidant and anti-carcinogenic properties in rats fed with beef tallow after AOM pretreatment.…”
Section: Discussionsupporting
confidence: 47%
“…It has long been approved for the prevention of hepatic and renal damage following acetaminophen overdose 22 . This well documented effect traditionally has been attributed to the restoration of intracellular glutathione levels 23,24 , required for detoxification of an acetaminophen-derived toxic metabolite. N-acetylcysteine also may attenuate the course of hepatorenal syndrome, a renal vasoconstrictive response of indeterminate nature that develops during advanced liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…sulphonamides and phenobarbitals, should be avoided. Administration of several cysteine delivery compounds, such as NAC, 2-oxothiazolidine-4-carboxylate (OTC; a 5-oxoproline analogue), methionine and S,N-diacetylcysteine monoethyl ester, increase the intracellular levels of GSH [61,62]. However, these compounds would generally be of limited value in raising GSH levels in GSS-deficient patients, as these patients are unable to form the tripeptide.…”
Section: Treatmentmentioning
confidence: 98%